МЕТОДЫ И ПРИЕМЫ ОБУЧЕНИЯ ДИАЛОГИЧЕСКОЙ РЕЧИ НА УРОКАХ ГАГАУЗСКОГО ЯЗЫКА И ЛИТЕРАТУРЫ В ОБРАЗОВАТЕЛЬНЫХ УЧРЕЖДЕНИЯХ РЕГИОНА/АТО ГАГАУЗИИ - Надежда КОЧАНЖИ (Moldova State University, 2020)
Articolul discută principalele tipuri și caracteristici ale vorbirii dialogice. Caracteristica vorbirii dialogice este dată. Pe baza experienței pedagogice, este descrisă o metodologie pentru formarea competențelor comunicative verbale, modalități de a depăși dificultățile pe care un profesor le întâmpină în lecția limbii și literaturii găgăuze în predarea vorbirii dialogice. Sunt indicate subiecte de vorbire care permit introducerea elevilor în situații de vorbire. Sunt prezentate câteva tipuri de activități, exerciții, jocuri, metode și tehnici pentru dezvoltarea competențelor comunicative în rândul studenților de la gimnaziu. METHODS OF TEACHING DIALOGICAL SPEECH IN THE LESSONS OF THE GAGAUZ LANGUAGE AND LITERATURE IN THE EDUCATIONAL INSTITUTIONS OF THE REGION/ATU OF GAGAUZIA The article discusses the main types and features of dialogic speech. The characteristic of dialogic speech is given. On the basis of pedagogical experience, a methodology for the formation of verbal communicative competencies is described, ways to overcome the difficulties that a teacher encounters in the lesson of the Gagauz language and literature when teaching dialogic speech. Speech topics that allow students to be introduced into speech situations are indicated. Some types of activities, exercises, games, methods and techniques for the development of communicative competencies among students of the gymnasium level are presented.